(untitled) (Research, Society and Development, 2022)
Bacuri is an Amazonian fruit with nutritional and functional potential. Such characteristics confer high perishability to the fruits. The drying of food products has been a principle to increase shelf life, as well as an alternative to the lack of market and high cost of storage. Thus, this work aimed to study the physical and physical-chemical characteristics of bacuri pulp in natura and elaborate foam, as well as to evaluate the physical and physical-chemical characteristics of the powders obtained by drying in a foam layer at temperatures of 50, 60 and 70°C. The foam was made from fresh pulp diluted in 50% water and addition of 2.5% of Emustab and 5.0% of Albumin for 15 minutes of agitation in a domestic planetary mixer, then subjected to to the drying process. To characterize the products, the water content, pH, acidity, lipids, total sugars, reducing sugars and non-reducing sugars were evaluated. For the color parameters L*, a* and b*, the Colorimeter version 5.5.1 was used. The process of converting bacuri pulp into foam causes a difference in some physical and physical-chemical attributes, and drying at 70 ºC is better suited to the phenomenon, consolidating the foam layer drying technique as a simple and effective method for development on an industrial scale.